Semantic web technologies in e-learning - Gonçalves, Vitor (2012)
The traditional view of learning puts most of the emphasis on face-to-face teaching and curriculum. It is very slow and expensive. Many people try to find e-Learning systems and learning objects on the Web. But that can be very difficult to find what we need with the actual search engines. How can someone fast and well in the Web? Our Proposal: Use Semantic Web technologies on the Development of virtual learning environments.